Some International Trade Factors for Great Britain, 1880-1913 - Silverman, A. G. (The Review of Economics and Statistics, 1931)
I N a previous article the derivation of monthly indexes of wholesale import and export prices for the United Kingdom, I880-I9I3, was described.' The present article deals with the results obtained in the statistical analysis of (i) import prices, export prices, and the ratio of import to export prices; (2) gold exports, imports, and excess of imports over exports; and (3) the value of United Kingdom produce exported. A necessarily brief discussion of possible inferences, explanations, and conclusions relating to the interpretation of the results obtained, with some supplementary data required for proper articulation, is presented.2 The two price indexes and their relative movements receive most attention. The export value series is selected for present purposes as picturing cyclical variations in British industry and foreign trade. The gold series are not only important in themselves as central data in international trade discussions, but also illustrate technical difficulties.A The fragmentary presentation of a few statistical series cannot reflect broad theoretical interests, nor the complexity of the interrelations involved in international trade phenomena and problems. A brief statement of the writer's general theoretical position may, therefore, be in order. Adoption of the dynamic, as opposed to the static, approach to economic problems is the unifying element in this position. The difference between these two is considered that between generalization through greater abstraction or simplification, and generalization which ties in particular cases by properly allowing for what occurs or may occur in time. The explanation must keep pace with the changing alternatives in a non-homogeneous economic complex of events; a generalized theory must be broad enough to allow for shifts in time (and the economic events ordered in it) and in points of vantage (assumptions), while at the same time building into its conceptional structure derivations of particular cases. Economic movements are held to be the resultants of a complex of interrelated factors, proceeding at variable rates. Not only are innumerable combinations possible, but the system is not even closed. Consequently, owing to the complexities it attempts to comprehend, the dynamic method must often be purely empirical. In inductive investigations of the theory of international prices and trade little consideration has been given to the question of the time within which verification may be expected. The result has often been a too tenuous connection between the statistical materials examined and the deductive theory. The pure theory is concerned with a logical sequence in which the period of time is that required for the full working out of the forces assumed to be in Qperation. The qualification at any given time or factors remaining equal performs the logical function of eliminating disturbances. This logic involves considerable abstraction from economic events and is perhaps I This REVIEW, Vol. XII, pp. I39-48. 2 The writer's chief interest in the study of British international trade, i88-i9I3, is in the restatement, as the first step towards their solution, of important problems in the theory of international trade and prices; and in contributing towards the development of a suitable technique statistical technique is only part of this for the solution of these and similar problems. International trade is viewed as only an aspect of trade in general, but, because of the separation of statistical materials, offering remarkable opportunities for analysis of economic realities. For example, the mechanism or perhaps thermodynamics whereby international shifts in purchasing power resulting from changes in relative demands or costs (supplies), or from credit creations considered in their proper economic context and not in vacuo, are related to changes in relative prices and price levels, appears to have some bearing on the problems connected with the dynamic phenomena (cyclical and secular) of domestic trade, and the way in which credit expansion starting with New York banks finds national expression. And the problems of mechanism and economic effects connected with rates of new capital issues, investment, savings and production, are in essence the same as those involved in capital exports. The relative timing of new bond issues and the utilization of their proceeds is not different from the process of foreign investment in relation to the creation of an export surplus. The late Professor Allyn A. Young has called attention to the domestic gold flows, cyclical in character, between the interior and New York which are essentially like international gold flows. 3 Sources of data. Import and export price indexes and related series: calculated by writer (see this REVIEW, Vol. XII, pp. I39-48). Value of exports of United Kingdom produce, data on gold movements, and value of iron and steel products exported; Trade and Navigation Reports for the United Kingdom. Sources of other data are indicated in text.